Multifaceted understanding of human nerve implants to design optimized electrodes for bioelectronics. (December 2022) - Valle, Giacomo; Aiello, Giovanna; Ciotti, Federico; Cvancara, Paul; Martinovic, Tamara; Kravic, Tamara; Navarro, Xavier; Stieglitz, Thomas; Bumbasirevic, Marko; Raspopovic, Stanisa
Abstract: Bioelectronic medicine is a promising venue for treatment of disabilities using implantable neural interfaces. Peripheral neurostimulation of residual nerves recently enabled multiple functional benefits in amputees. Despite the preliminary promising impact on patients' life, the over-time stability of implants and the related nerve reactions are unclear. To unveil the mechanisms and inform the design of better nerve-electrode interfaces, we engaged a multifaceted approach, merging functional responses from patients, their histological data, and corresponding computational modelling. Neurostimulation evoked different selective sensation locations and qualities over-time, with respective perceptual thresholds, that showed different degree of time stabilities dependent from the stimulating active sites. The histological analysis after explant showed mild tissue reactions, while electromechanically active sites and substrates remained conserved. Computational models, based on patients' histology, revealed the direct influence of the simulated tissue reaction to change of thresholds and type of perceived sensations. Novel insights of electrode biocompatibility was observed compared to animals and the increase of thresholds could be predicted computationally. This multifaced framework suggest that future intraneural implants should have easier implantation and higher biocompatibility counteracting the sensations changes through AI-based stimulations and electrode coatings.